2012
DOI: 10.1007/s10344-012-0613-7
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of heavy metals and PCBs in the tissues of European beavers (Castor fiber) captured in northeastern Poland

Abstract: European beavers (Castor fiber) from two regions were examined to identify exposure to persistent environmental contaminants. A reference group was comprised of six animals from the Forest Division of Srokowo, and an exposed group was comprised of five animals from the vicinity of a former military airport operated in 1918-1986-both from Warmia land in Poland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 20 publications
4
15
0
Order By: Relevance
“…Zalewski et al [50] in biceps femoris from wild beaver males captured in Northeastern Poland found similar concentration of Zn and Cu (45 and 1.0 mg kg −1 fresh tissue) compared to beaver semimembranosus hunted in Lublin region (Central-East Poland).…”
Section: Mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zalewski et al [50] in biceps femoris from wild beaver males captured in Northeastern Poland found similar concentration of Zn and Cu (45 and 1.0 mg kg −1 fresh tissue) compared to beaver semimembranosus hunted in Lublin region (Central-East Poland).…”
Section: Mineralsmentioning
confidence: 99%
“…The high zinc concentration in beaver muscles is related to high content of this element in tree leaves, bark, and cambium due to its (Zn +2 ) intensive uptake by both the root system and the leaves [50].…”
Section: Mineralsmentioning
confidence: 99%
“…Elevated levels of cadmium in tissues have been reported in multiple studies in both polluted areas and areas considered “ecologically clean” (Fimreite et al ; Giżejewska et al ; Giżejewska et al ; Nolet et al ; Zalewski et al ). Fimreite et al () found that beavers’ preferred plant species (aspen [ Populus spp.…”
Section: Exposure To Anthropogenic Pollutantsmentioning
confidence: 99%
“…In both otters and beavers, the focus of research has been on tissue and body burdens as a result of mercury exposure in river otters and cadmium exposure in beavers due to their food preferences. Accumulation of metals (arsenic, cadmium, lead, mercury, selenium, copper, manganese, and zinc) and PCBs in both species can be age‐specific (Fimreite et al ; Giżejewska et al ; Hillis and Parker ), sex‐specific (Walker et al ), and tissue‐dependent (Chadwick ; Kang et al ; Wren ; Zalewski et al ).…”
Section: Exposure To Anthropogenic Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation